Using a Project Blog to Promote Student Learning and Reflection - Worthington, Paisley; Reniers, Jennifer; Lackeyram, Dale; Dawson, John (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2018)
Research on the use of blogs in higher education suggests that students who blog as part of a course requirement demonstrate increased reflection, heightened feelings of connection, and increased course-related knowledge. Blogging provides a promising medium for students to engage in reflection on their participation in a cooperative education work term. Blogging can help guide a project by providing an encouraging place for team members to communicate clearly, document their work and other resources, and brainstorm ideas. In this paper, we describe a qualitative analysis of blog posts written by three students during a co-op placement. The students used the blog extensively and with multiple purposes: to reflect, to communicate, to brainstorm ideas, to evaluate literature, and to document team creations. We discuss the characteristics of the project and blog that may have contributed to its extensive use and provide recommendations for individuals interested in implementing a blog in similar projects.